Fernbahnhöfe an Flughäfen und ihre Wirkung aus der Sicht der Hauptakteure. - Meyer, Carsten E. (Deutscher Verkehrs-Verl., 2004)
Die Verknüpfung des Luftverkehrs mit dem Fernbahnverkehr ist in den vergangenen Jahren europaweit intensiv vorangetrieben worden. Aktuelles Beispiel ist der Bahnhof am Flughafen Köln/Bonn. Unklar ist jedoch, welche beteiligten Akteure von den aufwändigen Fernbahnhöfen an Flughäfen tatsächlich profitieren. In dem Beitrag wird die Wirkung dieser Verknüpfung aus der Sicht von Flughafengesellschaft, Fluggesellschaften und Bahngesellschaft empirisch mit Hilfe des Discrete choice-Verfahrens bewertet. difu

In recent years, there has been a notable drive towards linking up air transport and long distance rail services across Europe, the railway station at Cologne/Bonn airport being the newest case. As yet, however, there is no clear evidence as to which business partner is profiting from such expensive-to-build railway stations at airports. The report systematically analyses the efficacy of the rail-air link-up and evaluates the views of concerned airport authorities, air carriers and railway companies in an empirical manner by applying the 'discrete choice' method. To pinpoint the relevant advantages and disadvantages, the principal business partners involved have to be investigated thoroughly. In the case of airports, their role of hub or feeder is reviewed as is their usage. From a global viewpoint, railway stations at airports handling long distance services are not a sensible proposition because of the vastly divergent interests of the actors concerned. difu
Keywords: Öffentlicher Verkehr; Personenverkehr; Luftverkehr; Eisenbahnverkehr; Fernverkehr; Wirkungsanalyse; Verkehrsmittelwahl; Verkehrsunternehmen; Verkehrsanbindung; Flughafen; Flughafenanbindung; Fernbahnhof; Reiseverkehr; Verkehrsstrom; Verkehrsträger